Pengaruh Motivasi, Disiplin Kerja, dan Lingkungan Kerja Terhadap Kepuasan Kerja pada Pegawai Perumda Manuntung Sukses Kota Balikpapan - Rahya Nasywa Balqis; Tutik Yuliani; Imam Arrywibowo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of motivation, work discipline, and work environment on job satisfaction among employees of Perumda Manuntung Sukses Balikpapan. The research employed a quantitative approach with a saturated sampling technique involving 45 employees. Data were collected through observation, interviews, and Likert-scale questionnaires and analyzed using Partial Least Square (PLS) with SmartPLS software. The findings reveal that motivation has a positive and significant effect on job satisfaction, followed by work discipline and work environment, which also show positive and significant influences. The R-Square value of 0.839 indicates that 83.9% of job satisfaction is explained by the three variables, with motivation as the most dominant factor.